RIGHTS AT WORK OF MEDICAL WORKERS DURING A STATE OF EMERGENCY - Reljanović, Mario; Misailović, Jovana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
During the declared state of emergency due to the COVID-19 virus pandemic in the Republic of Serbia in 2020, medical workers performed their tasks in a special regime of work, with specific restrictions in accordance with the Decision on the state of emergency, the Law on Defence, the Law on the Military, Labour and material obligation, as well as decisions of the Government of the Republic of Serbia and the Ministry of Health. Their employment position was complex and their work duties were specifically organised. Research includes normative analysis of their employment status during the state of emergency, with special reference to some labour rights: working hours, work schedule, change of place of work, work obligation regime. It points to the flexibility of work in the state of emergency, the good and bad characteristics of the current legal framework, as well as the good and bad practice observed in this regard. Special attention is given to the illegal prolongation of the duration of emergency measures even after the termination of the state of emergency. Recommendations are given for better regulation of these issues, as well as for strengthening the mechanisms of protection of labour rights of medical workers, in specific circumstances caused by medical reasons.